Comparison of influence of eight-week preparatory period on changes in selected morphological parameters in seventeen-year-old football and ice hockey players - Sigmund, M.; Lehnert, M.; Kudlacek, M. (Journal of Physical Education and Sport, 2015)
Sport training in elite athletes has an effect on the degree of adaptation of many body systems. One of the important categories, where adaptation changes can be observed, is the area of somatic characteristics. The aim of this paper is to identify the changes in selected morphological parameters in seventeen-year-old football and ice hockey players with regard to eight-week fitness training. The research included young football players (n = 21) and ice hockey players (n = 39) aged 17.00 to 17.99 of top performance level. To determine body composition by the BIA method we used the Tanita BC-418 MA instrument. The BIA measurement and anthropometric examination were carried out in accordance with the recommended domestic and international standards of the International Society for the Advancement of Kinanthropometry. During the investigation we monitored nonsignificant changes in the morphological parameters with a small to medium effect size in seventeen-year-old boys of both sports specializations with regard to the duration of sport training during an eight-week period. Larger differences in the changes in the monitored morphological parameters were observed in young ice hockey players compared with football players. The presented outcomes document specific changes in selected morphological parameters with respect to intensive fitness training during an eight-week period in seventeen-year-old football and ice hockey players The findings enrich the theoretical knowledge in this area and are well applicable in the optimization of the training process of young athletes of the selected specializations